A simple method for rapid screening and diagnosis of common organic acidemias: quantitative detection of serum and urine organic acid profiles based on liquid chromatography-tandem mass spectrometry - Jin, Lizi; Liu, Zhenni; Zeng, Jie; Zhao, Haijian; Zhang, Jiangtao; Zhu, Bo; Zhang, Yu; Zhang, Tianjiao; Zhang, Chuanbao (Analytical and bioanalytical chemistry, 2022)
Organic acid (OA) analysis is a specific test for inherited metabolic disorders (IMDs); however, the previous detection methods are laborious and costly. This study aims to develop a rapid method for the simultaneous quantification of serum and urine OA profiles. The method was established based on the liquid chromatography-tandem mass spectrometry (LC–MS/MS) technique. The specificity, sensitivity, robustness, and accuracy of the established method were validated. Fifteen healthy subjects and nine IMD patients were measured for clinical validation. OAs with their intrinsic isomers were completely separated. The LC–MS/MS analysis time was 5.5 min. Calibration curves were linear within the ranges of 27.00 μg/g for all OAs. The average correlation relationship ( R ) varied from 0.9891 to 0.9998. The limit of detection and limit of quantification varied from 0.003 to 0.07 μg/g and 0.006 to 0.08 μg/g, respectively. No obvious carryover was observed. The intra-assay, inter-assay, and total imprecisions were 1.22–4.14%, 0.90–5.20%, and 1.67–5.90%, respectively. The mean spiked recovery at the three levels varied from 94.31 to 106.68%. The matrix effects can be compensated for by internal standard correction. Nine IMD patients were identified. A robust LC–MS/MS method for the rapid determination of serum and urine OA profiles without derivatization or liquid–liquid extraction was developed and validated. The analysis of five common OAs can be completed in short minutes. This innovative LC–MS/MS method for OA profiles may present its potential in future rapid screening and diagnosis of IMDs. Graphical abstract